2019
DOI: 10.1093/mnras/stz3054
|View full text |Cite
|
Sign up to set email alerts
|

A profile in FIRE: resolving the radial distributions of satellite galaxies in the Local Group with simulations

Abstract: While many tensions between Local Group (LG) satellite galaxies and ΛCDM cosmology have been alleviated through recent cosmological simulations, the spatial distribution of satellites remains an important test of physical models and physical versus numerical disruption in simulations. Using the FIRE-2 cosmological zoom-in baryonic simulations, we examine the radial distributions of satellites with M * > 10 5 M around 8 isolated Milky Way-(MW) mass host galaxies and 4 hosts in LG-like pairs. We demonstrate that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
140
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(154 citation statements)
references
References 121 publications
(158 reference statements)
11
140
2
1
Order By: Relevance
“…Semi-empirical models that account for these effectsalong with realistic satellite detection criteria-find that the observed satellite population is consistent with cold, collisionless dark matter (e.g., Jethwa et al 2018;Kim et al 2018;Newton et al 2018;Bose et al 2019;Nadler et al 2019aNadler et al , 2019b. Likewise, hydrodynamic simulations that self-consistently model galaxy formation in a cosmological context produce luminosity functions and radial distributions of satellites that are broadly consistent with observations of the Milky Way system (e.g., Wetzel et al 2016;Garrison-Kimmel et al 2019;Samuel et al 2020). In concert, extremely high-resolution simulations of isolated ultra-faint systems suggest that low-mass dwarfs may be abundant (Wheeler et al 2019).…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Semi-empirical models that account for these effectsalong with realistic satellite detection criteria-find that the observed satellite population is consistent with cold, collisionless dark matter (e.g., Jethwa et al 2018;Kim et al 2018;Newton et al 2018;Bose et al 2019;Nadler et al 2019aNadler et al , 2019b. Likewise, hydrodynamic simulations that self-consistently model galaxy formation in a cosmological context produce luminosity functions and radial distributions of satellites that are broadly consistent with observations of the Milky Way system (e.g., Wetzel et al 2016;Garrison-Kimmel et al 2019;Samuel et al 2020). In concert, extremely high-resolution simulations of isolated ultra-faint systems suggest that low-mass dwarfs may be abundant (Wheeler et al 2019).…”
Section: Introductionsupporting
confidence: 56%
“…Such an assumption breaks down if a large population of extremely low-surface-brightness systems exists (e.g., satellites like Crater II and Antlia II). A population of large, luminous, and distant Milky Way satellites has been suggested to resolve the observed radial distribution discrepancy between the satellite populations of the Milky Way and Andromeda (e.g., Yniguez et al 2014;Samuel et al 2020). In addition, we assumed that the intrinsic properties of satellites (e.g., luminosity and half-light radius) are independent of heliocentric distance.…”
Section: Satellite Luminosity Functionmentioning
confidence: 99%
“…• Tensions between the observed and predicted radial distributions of satellites. The radial distribution of Milky Way satellites appears to stand in contrast with the predictions of ΛCDM models, in the sense that it appears to be more centrally-concentrated than typical simulated Milky Way-mass systems (Kravtsov et al 2004;Yniguez et al 2014;Samuel et al 2020). Previous studies have shown that the incorporation of important baryonic physics can help to reconcile this tension (e.g., Kravtsov et al 2004;Macciò et al 2010;Font et al 2011;Starkenburg et al 2013).…”
Section: Introductionmentioning
confidence: 80%
“…This highlights the importance of having a large sample if we hope to distinguish between feedback models. Hydro-simulation suites that consist of on the order of ten MW/M31 analogues would struggle in revealing the aforementioned differences (Samuel et al 2020). Similarly, on the observational side, surveys of more MW/M31 analogues are needed.…”
Section: Effects Of Different Baryonic Physicsmentioning
confidence: 99%